Therapeutic Effects of Hydrogel Formulations Incorporating Troxipide Nanoparticles on Oral Mucositis in Hamsters - Kadowaki R; Ogata F; Nishida M; Komatsu M; Otake H; Nakazawa Y; Yamamoto N; Kawasaki N; Nagai N (Dove Medical Press, 2023)
Reita Kadowaki,1 Fumihiko Ogata,1 Miku Nishida,1 Miri Komatsu,1 Hiroko Otake,1 Yosuke Nakazawa,2 Naoki Yamamoto,3 Naohito Kawasaki,1 Noriaki Nagai1 1Faculty of Pharmacy, Kindai University, Higashi-Osaka, Osaka, Japan; 2Faculty of Pharmacy, Keio University, Minato-ku, Tokyo, Japan; 3Support Office for Bioresource Research, Research Promotion Headquarters, Fujita Health University, Toyoake, Aichi, JapanCorrespondence: Noriaki Nagai, Faculty of Pharmacy, Kindai University, 3-4-1 Kowakae, Higashi-Osaka, Osaka, 577-8502, Japan, Tel +81 6 4307 3638, Fax +81 6 6730 1394, Email nagai_n@phar.kindai.ac.jpPurpose: Medical therapies, such as the use of anti-inflammatory agents, are commonly used for the treatment of oral mucositis (OM). However, these treatments have limited efficacy in treating severe cases of OM. In this study, we aimed to develop a carbopol gel incorporating troxipide (TRO) nanoparticles and methylcellulose (TRO-NP gel) and demonstrate its efficacy in accelerating wound healing in a hamster model of OM (OM model) induced by acetic acid injection.Methods: TRO nanoparticles were prepared using bead milling. The crystalline form was determined by powder X-ray diffraction, and the particle size was measured using a NanoSight LM10 instrument. The drug release was determined using a Franz diffusion cell, and the hamsters injected with acetic acid were selected to evaluate the therapeutic effect of OM.Results: After preparing TRO nanoparticles, we observed a mixture of crystals and amorphous TRO, and the particle size of TRO in the TRO-NP gel ranged from 50 to 280 nm. The TRO-NP gel exhibited a more uniform TRO distribution and viscosity compared to the Carbopol gel containing TRO microparticles (TRO-MP gel). However, the solubility of TRO was comparable in both TRO-MP and TRO-NP gels. The TRO-NP gel released a higher amount of TRO than that from the TRO-MP gel, with detectable release of TRO nanoparticles. TRO levels in the cheek pouches of hamsters treated with TRO-NP gel were higher than those treated with TRO-MP gel. The increased TRO levels in the cheek pouches of hamsters treated with TRO-NP gel were attenuated by treatment with 40 μM dynasore, an inhibitor of clathrin-dependent endocytosis (CME). Moreover, the therapeutic effect of the TRO-NP gel was superior to that of the TRO-MP gel in the hamster model of OM.Conclusion: We have designed a TRO-NP gel, and this gel showed excellent TRO delivery into the cheek pouch tissue through the CME pathway. Moreover, the TRO-NP gel treatment enhanced wound healing after acetic acid injection. Keywords: troxipide, nanoparticle, oral mucositis, hydrogel, endocytosis